Negative Transfer in Indonesian Youths’ English Grammatical Errors on Threads - Azzahra, Stevanny Nabila; Prasetyo, Rayhan Safaruddin; Hidayahtulloh, Achmad Bima; Indrawan, Fani (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to describe the profile of young Indonesians who make grammatical errors in their social media posts on Threads, focusing on the phenomenon of negative transfer from the first language (L1) to the second language (L2) as described in Robert Lado’s Contrastive Analysis Hypothesis. This study explores how L1 interference affects the respondents’ English language production through a qualitative descriptive approach. Research data were obtained from five Threads posts uploaded by the respondents as well as online interviews to deepen the analysis and were then analyzed to identify forms of grammatical errors reflecting negative transfer from L1 to L2. The results indicate that although the respondents had studied English in formal education for approximately six years, fundamental grammatical errors still frequently occurred, suggesting that the influence of the first language remains significant in the process of second-language production, particularly in the context of informal use on social media.